A review of the genus Cyana Walker, 1854 (Lepidoptera, Erebidae, Arctiinae) from Cambodia, with description of new species - Bayarsaikhan, Ulziijargal; Bae, Yang-Seop (Zootaxa, 2016)
Genus Cyana Walker, 1854, with 17 species in Cambodia, is reviewed. Among them, Cyana angkorensis Bayarsaikhan & Bae, sp. n. is described as new to science and 7 species are newly recorded from Cambodia. A key to the Cambodian species of the genus Cyana with illustrations of adults and genitalia is presented.